Thermal distortions of multichannel laser radiation - Kanev F. Yu. Fedor Yurievich; Makenova N. A. Nailya Altynkhanovna; Lukin V. P. Vladimir Petrovich; Antipov O. L. Oleg Leonidovich; Veretekhin I. D. Igor Dmitrievich (2017, 2017)
Title screen